MENYELISIK PERMASALAHAN IMPLEMENTASI GREEN BANKING - Lestari, Agustin Dwi; Kartika, Kartika; Aprillianto, Bayu (ANALISIS, 2024)
The environment plays an important role in human life. As humans, we are also very dependent on the environment. The need to survive in all fields is a side effect of financial development or development that results in climate change and also environmental damage caused by various industries. Existing companies will certainly generate impacts from activities or activities carried out related to the environment. Banking companies in these circumstances take an important role with the implementation of environmentally friendly programs, namely green banking. This research aims to find out and examine more deeply related to green banking run by Bank Mandiri Lumajang Branch Office related to how lending and also environmentally sound company operations. This research uses a qualitative method with a case study method approach that aims to provide an understanding of the role of green banking in Bank Mandiri companies. The research found an important role in the implementation of green banking carried out by the Bank Mandiri Lumajang Branch Office.